Towards real-time identification of cosmic rays with LOw-Frequency ARray radio antennas - Bonardi, Antonio; Buitink, Stijn; Corstanje, Arthur; Enriquez, J. Emilio; Falcke, Heino; Hörandel, Jörg R.; Mitra, Pragati; Mulrey, Katie; Nelles, Anna; Rachen, Jörg Paul; Rossetto, Laura; Schellart, Pim; et al. (EPJ Web of Conferences, 2017)
Cosmic rays entering the Earth's atmosphere produce Extensive Air Showers, which emit a radio signal through Geo-magnetic radiation and Askaryan emission. At the present time, one of the biggest challenges for assessing the Radio detection as a valuable technique for Cosmic-ray observation is to identify in real-time the very short (less than 100 ns) radio signals over the background noise. In this work, we present the latest updates on the real-time identification of radio signals from Extensive Air Showers by using the data from LOFAR Low Band Antenna stations, which are sensitive in the 30-80 MHz region.
CRIS-Team Scopus Importer:2023-08-15